Learning about immigrant and migrant readers, transforming libraries: Spanish-speaking readers in North America - Dali, Keren (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2021)
Drawing on data from the qualitative survey study of avid immigrant and migrant Spanish-speaking readers residing in Canada and the U.S., this paper looks at their use of libraries, specifically, in the context of leisure reading. Acknowledging a gap in current research on Spanish-speaking immigrants/migrants, the study focuses on avid lifelong readers rather than information seekers; achieves an understanding of their reading practices and interactions with libraries in the context of their pre-migration experiences; and highlights readers’ suggestions for the improvement of collections, spaces, services, and community engagement. Practical suggestions are made for public, academic, and special libraries.